Bijak Menjadi Orang Tua di Era Digital: Penyuluhan di Kelompok Pemberdayaan Kesejahteraan Keluarga (PKK) Sendari - Nurnawati, Erna Kumalasari; Arbintarso, Ellyawan Setyo (LPPM IST AKPRIND Yogyakarta, 2021)
Information and Communication Technology (ICT) has been used in every aspect of life. Children are familiar with ICT, both for learning and playing activities. The widespread use of ICT among children must be accompanied by parents' assistance, and supervision to obtain optimal benefits and minimize the disadvantages of using ICT. The community service program is carried out for mothers who are members of Kelompok Pemberdayaan Kesejahteraan Keluarga (PKK) in Sendari Tirtoadi, Sleman Yogyakarta by using the method of socialization and outreach to parents (especially mothers) about how to assist children in using electronic ICT devices, both for activities study and other activities and followed by the procurement of a survey of 25 participants. The results of a survey conducted on 25 participants obtained information that 100% of children have at least one ICT-based communication tool, 100% of children have used ICT equipment, 83% of parents do not follow their children's social media accounts or check their children's gadgets and 75% of people parents do not provide assistance to children's activities in using ICT equipment. These results indicate the need for socialization of how to be wise parents in the digital era, especially in assisting children in using ICT. The role of parents in mentoring is essential so that children can use IT well.